2020
DOI: 10.1101/2020.03.04.975748
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure and mechanism of a primate ferroportin

Abstract: 4Ferroportin is the only cellular iron exporter in human and essential for iron homoeostasis.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…These remain to be investigated experimentally, but of note, Rishi and colleagues recently reported on the intracellular localization of ferroportin dimers, and concluded that both the carboxy-and amino-termini of the protein are intracellular [109]. As cited earlier, the details of hepcidin's own interaction sites with ferroportin remain the subject of different structural determination projects [12,18,108]. Relatedly, and of interest, Neves and colleagues, using experiments on iron overload in European bass (Dicentrarchus labrax), have discussed the functional partnership between hepcidin and ferroportin from an evolutionary perspective and suggested that this may "open new possibilities for the pharmaceutical use of selected fish […] hepcidins during infections, with no impact on iron homeostasis" [90,91].…”
Section: Potential Leads For Coronavirus Research Hepcidin-like Motifmentioning
confidence: 99%
See 2 more Smart Citations
“…These remain to be investigated experimentally, but of note, Rishi and colleagues recently reported on the intracellular localization of ferroportin dimers, and concluded that both the carboxy-and amino-termini of the protein are intracellular [109]. As cited earlier, the details of hepcidin's own interaction sites with ferroportin remain the subject of different structural determination projects [12,18,108]. Relatedly, and of interest, Neves and colleagues, using experiments on iron overload in European bass (Dicentrarchus labrax), have discussed the functional partnership between hepcidin and ferroportin from an evolutionary perspective and suggested that this may "open new possibilities for the pharmaceutical use of selected fish […] hepcidins during infections, with no impact on iron homeostasis" [90,91].…”
Section: Potential Leads For Coronavirus Research Hepcidin-like Motifmentioning
confidence: 99%
“…Finally, hepcidin binds to and mediates the degradation of ferroportin (encoded by the SLC40A1 / FPN1 gene), the only known cellular iron exporter. The structural details of this interaction are being mapped and studied in ever more detail [18,88,108].…”
Section: The Hepcidin Proteinmentioning
confidence: 99%
See 1 more Smart Citation